A kind of water-based two-component polyurethane varnish and its preparation method and use method

By introducing modified acrylate emulsions, quaternary ammonium cage-shaped silicone and amphiphilic silica nanosheets into aqueous two-component polyurethane varnish, the existing varnish lacks water resistance and UV aging resistance in humid environments, achieving more stable performance and longer service life.

CN119060622BActive Publication Date: 2025-04-25ZHONGSHAN UBEST TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411294537.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-04-25
Estimated Expiration
2044-09-14

AI Technical Summary

Technical Problem

The existing water-based two-component polyurethane varnish has weak water resistance in humid environments and has insufficient anti-UV aging performance, resulting in unstable gloss and color of the paint film under long-term ultraviolet irradiation.

Method used

By preparing an aqueous two-component polyurethane varnish containing a modified acrylate emulsion, a quaternary ammonium cage silicone and an amphiphilic silica nanosheet, the modified acrylate emulsion was prepared from the reaction of methyl methacrylate, butyl acrylate, hydroxypropyl methacrylate, quaternary ammonium cage silicone and amphiphilic silica nanosheets, the water resistance and UV aging resistance of the varnish were enhanced.

Benefits of technology

The aqueous two-component polyurethane varnish maintains stable performance in humid environments and maintains the gloss and color of the paint film under long-term ultraviolet irradiation, extending its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005045537060000121
    Figure BDA0005045537060000121
Patent Text Reader

Abstract

The invention discloses a water-based two-component polyurethane varnish and a preparation method and a method of use thereof, and relates to the field of varnish. The water-based two-component polyurethane varnish prepared by the present invention comprises component A and component B, wherein component A comprises pure water, a wetting agent, a defoamer, and a modified acrylic emulsion; component B comprises an isocyanate curing agent and pure water; wherein the modified acrylic emulsion is prepared by an acrylic monomer, a quaternary ammonium salt caged siloxane, and an amphiphilic silica nanosheet; the quaternary ammonium salt caged siloxane is prepared by reacting a caged siloxane precursor obtained by nonafluorohexyltrimethoxysilane with 3-chloropropyltrichlorosilane, and then reacting with 4-vinylpyridine; the amphiphilic silica nanosheet is prepared by reacting a silica nanosheet with dodecyltrimethoxysilane, reacting with cyanuric chloride, and then reacting with sodium sulfosalicylate. The water-based two-component polyurethane varnish prepared by the present invention has good water resistance, antibacterial properties, and anti-ultraviolet aging properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of varnishes, in particular to a water-based two-component polyurethane varnish and a preparation method and a use method thereof. Background Art

[0002] Water-based two-component polyurethane varnish combines the excellent properties of water-based varnish and traditional solvent-based polyurethane varnish, and is increasingly favored by consumers. It has excellent mechanical properties, room temperature curing properties and environmental protection properties, and can be widely used in automobiles, wood, plastics, leather and other coatings.

[0003] Although water-based two-component polyurethane varnish has the above-mentioned advantages, it also has some significant disadvantages, such as relatively weak water resistance and easy peeling and cracking in a humid environment; for some outdoor use scenarios, a varnish is required that can maintain the gloss and color stability of the paint film under long-term ultraviolet radiation. Therefore, in order to overcome these shortcomings, it is necessary to prepare a new type of water-based two-component polyurethane varnish, which should have good water resistance and be able to maintain stable performance in a humid environment; at the same time, it should also have excellent anti-ultraviolet aging performance, thereby extending the service life; such a varnish will be more widely applicable to various occasions requiring high weather resistance and antibacterial properties. Summary of the invention

[0004] The purpose of the present invention is to provide a water-based two-component polyurethane varnish and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A water-based two-component polyurethane varnish comprises a component A and a component B, wherein the component A comprises pure water, a wetting agent, a defoaming agent, and a modified acrylic ester emulsion; and the component B comprises an isocyanate curing agent and pure water;

[0007] As an optimization, the modified acrylic ester emulsion is prepared by reacting methyl methacrylate, butyl acrylate, hydroxypropyl methacrylate, quaternary ammonium salt caged siloxane, and amphiphilic silica nanosheets.

[0008] As an optimization, the quaternary ammonium salt caged siloxane is prepared by obtaining a caged siloxane precursor from nonafluorohexyltrimethoxysilane, reacting the caged siloxane precursor with 3-chloropropyltrichlorosilane to obtain a caged siloxane, and then reacting the caged siloxane with 4-vinylpyridine.

[0009] As an optimization, the amphiphilic silica nanosheets are obtained by reacting tetraethoxysilane and 3-aminopropyltriethoxysilane to obtain silica nanosheets, which are then reacted with dodecyltrimethoxysilane to obtain modified silica nanosheet precursors, which are then reacted with cyanuric chloride to obtain modified silica nanosheets, which are then reacted with sodium sulfosalicylate to obtain the prepared product.

[0010] A method for preparing a water-based two-component polyurethane varnish comprises the following preparation steps:

[0011] (1) nonafluorohexyltrimethoxysilane, tetrahydrofuran, pure water, and sodium hydroxide are mixed uniformly in a mass ratio of 1: (50-60): (0.06-0.08): (0.04-0.05), heated to 70° C. and refluxed for reaction for 4-5 hours, cooled to room temperature and stirred for 14-15 hours, and the tetrahydrofuran is removed by vacuum rotary evaporation, and dried at 40° C. for 22-24 hours to obtain a cage-type siloxane precursor;

[0012] (2) mixing a cage-type siloxane precursor, triethylamine, and tetrahydrofuran in a mass ratio of 1:(0.3-0.5):(20-30) to obtain a cage-type siloxane precursor solution, and mixing 3-chloropropyltrichlorosilane and tetrahydrofuran in a mass ratio of 1:(10-12) to obtain a cage-type siloxane precursor solution, and adding the mixture dropwise to the cage-type siloxane precursor solution at a rate of 1 mL / min at 0° C. After the addition is completed, the reaction is continued for 4-5 hours, and the temperature is raised to room temperature and the reaction is continued for 12-14 hours. The filtrate is filtered and the tetrahydrofuran in the filtrate is removed by vacuum rotary evaporation, and the mixture is washed with methanol for 3-4 times, and dried at 40° C. for 22-24 hours to obtain a cage-type siloxane;

[0013] (3) mixing cage-type siloxane, potassium carbonate, 4-vinylpyridine and chloroform in a mass ratio of 1: (0.3-0.5): (0.7-0.9): (15-20), heating to 70-80° C., reflux reaction for 24 h, cooling to room temperature, filtering and washing with chloroform 3-4 times, and drying at 40° C. for 22-24 h to obtain quaternary ammonium cage-type siloxane;

[0014] (4) mixing silica nanosheets and toluene in a mass ratio of 1:(150-160), adding 2-3 times the mass of silica nanosheets of dodecyltrimethoxysilane and 0.1-0.3 times the mass of silica nanosheets of triethylamine under nitrogen protection, reacting at 80° C. for 24 h, filtering and washing with toluene 4-5 times, and drying at 40° C. for 22-24 h to obtain a modified silica nanosheet precursor;

[0015] (5) Mixing the modified silica nanosheet precursor and toluene in a mass ratio of 1:(150-160), adding 5-6 times the mass of cyanuric chloride of the silica nanosheet under nitrogen protection, reacting at 25-30° C. for 10-12 h, filtering and washing with toluene 4-5 times, and drying at 40° C. for 22-24 h to obtain the modified silica nanosheet;

[0016] (6) under nitrogen protection, the modified silica nanosheets, chlorobenzene, and anhydrous aluminum chloride are mixed in a mass ratio of 1: (150-160): (5-6), and under nitrogen protection, 9-10 times the mass of sodium sulfosalicylate of the modified silica nanosheets is added, reacting at 30-40° C. for 15-17 hours, filtering and washing with toluene 4-5 times, and drying at 40° C. for 22-24 hours to obtain amphiphilic silica nanosheets; the amphiphilic silica nanosheets and pure water are mixed in a mass ratio of 1: (20-30) to obtain an amphiphilic silica nanosheet dispersion;

[0017] (7) ammonium persulfate and pure water are mixed in a mass ratio of 1:(10-20) to obtain an initiator solution; in parts by mass, 20-30 parts of methyl methacrylate, 20-30 parts of butyl acrylate, 5-10 parts of hydroxypropyl methacrylate, 10-20 parts of quaternary ammonium salt caged siloxane, 10-20 parts of modified silica nanosheet dispersion, 50-60 parts of pure water, and 3-5 parts of the initiator solution. Methyl methacrylate, butyl acrylate, hydroxypropyl methacrylate, quaternary ammonium salt caged siloxane, amphiphilic silica nanosheet dispersion and pure water are mixed, and stirred for 1-2 hours under nitrogen protection at a stirring speed of 500 rpm / min to obtain a pre-emulsion; 20% of the pre-emulsion and an initiator solution are stirred at a mass ratio of 1:(0.1-0.2) at 60-70° C. for 10-12 hours at a stirring speed of 200 rpm / min, and the temperature is raised to 80-82° C., and the remaining 80% of the pre-emulsion is added dropwise at a dropping rate of 1 mL / min. After the addition is completed, the temperature is continued to be raised to 90-92° C., and the temperature is cooled to room temperature after being kept for 40-50 minutes, and the pH is adjusted to 6-7 using 25wt% ammonia water to obtain a modified acrylate emulsion;

[0018] (8) Weighing 15-25 parts of pure water, 0.05-0.1 parts of wetting agent, 0.1-0.3 parts of defoaming agent, and 60-70 parts of modified acrylic emulsion by weight; mixing the pure water, wetting agent, defoaming agent, and modified acrylic emulsion, and stirring at 500-600 r / min for 20-30 min to obtain component A;

[0019] (9) Weigh 60-70 parts by mass of an isocyanate curing agent and 40-50 parts by mass of pure water, and stir the isocyanate curing agent and pure water at 500-600 r / min for 20-30 min to obtain component B;

[0020] (10) Component A and component B are mixed in a mass ratio of (4-5):1 and stirred evenly to obtain a water-based two-component polyurethane varnish.

[0021] As an optimization, the preparation method of the silica nanosheets in step (4) is as follows: sodium dodecyl sulfate and pure water are mixed in a mass ratio of 1:3, and the pH is adjusted to 3 with a 2 mol / L hydrochloric acid aqueous solution to obtain an aqueous phase, tetraethoxysilane, 3-aminopropyltriethoxysilane, and n-decane-toluene solution are mixed in a mass ratio of 1:(0.15-0.2):(5-6) to obtain an oil phase, the aqueous phase and the oil phase are mixed in a mass ratio of 1:0.25, stirred at a speed of 1000 rpm / min, and then heated to 70°C, reacted for 12 hours, centrifuged at a speed of 5000 r / min for 10 minutes, and washed 3-4 times with anhydrous ethanol to obtain silica hollow microspheres, and the silica hollow microspheres are crushed using a cell crusher. The operating parameters of the cell crusher are working for 2 seconds, pausing for 2 seconds, working time for 60 minutes, and power of 400 W. The crushed silica hollow microspheres are dried at room temperature for 24 hours to obtain silica nanosheets.

[0022] As an optimization, the n-decane-toluene solution is prepared by mixing n-decane and toluene in a mass ratio of 1:1.

[0023] As an optimization, the amounts of methyl methacrylate, butyl acrylate, hydroxypropyl methacrylate, quaternary ammonium caged siloxane, modified silica nanosheet dispersion, pure water, and initiator solution in step (7) are: by mass, 20-30 parts of methyl methacrylate, 20-30 parts of butyl acrylate, 5-10 parts of hydroxypropyl methacrylate, 10-20 parts of quaternary ammonium caged siloxane, 10-20 parts of modified silica nanosheet dispersion, 50-60 parts of pure water, and 3-5 parts of initiator solution.

[0024] As an optimization, the wetting agent model in step (8) is Hydropalat 140; the defoaming agent model is BYK-024.

[0025] As an optimization, the isocyanate curing agent model in step (9) is XP-2655.

[0026] The present invention also provides a method for using the water-based two-component polyurethane varnish prepared according to the preparation method of the water-based two-component polyurethane varnish. The method for using is: the water-based two-component polyurethane varnish is applied to a substrate by roller coating or spraying. The water-based two-component polyurethane varnish needs to be prepared and used immediately, and the coating is completed within 0-2 hours.

[0027] The water-based two-component polyurethane varnish prepared by the invention comprises component A and component B, wherein component A comprises pure water, a wetting agent, a defoaming agent and a modified acrylic ester emulsion; component B comprises an isocyanate curing agent and pure water; the modified acrylic ester emulsion is prepared by reacting methyl methacrylate, butyl acrylate, hydroxypropyl methacrylate, quaternary ammonium salt caged siloxane and amphiphilic silica nanosheets; the quaternary ammonium salt caged siloxane is prepared by reacting nonafluorohexyltrimethoxysilane to obtain a caged siloxane precursor, the caged siloxane precursor reacts with 3-chloropropyltrichlorosilane to obtain a caged siloxane, and the caged siloxane reacts with 4-vinylpyridine to obtain the caged siloxane; the amphiphilic silica nanosheet is prepared by reacting tetraethoxysilane and 3-aminopropyltriethoxysilane to obtain a silica nanosheet, the silica nanosheet reacts with dodecyltrimethoxysilane to obtain a modified silica nanosheet precursor, the modified silica nanosheet reacts with cyanuric chloride to obtain a modified silica nanosheet, and the modified silica nanosheet reacts with sodium sulfosalicylate to obtain the modified silica nanosheet.

[0028] Firstly, nonafluorohexyltrimethoxysilane is used to obtain a cage siloxane precursor, and the cage siloxane precursor is reacted with 3-chloropropyltrichlorosilane to obtain a cage siloxane containing nonafluorohexyl and monochloropropyl, and then reacted with 4-vinylpyridine to form a quaternary ammonium salt, and a double bond is introduced into the cage siloxane for subsequent polymerization with an acrylic ester monomer; the fluorine atom has a large electronegativity, a small radius, and a large bond energy, and the fluorine-containing monomer polymer has excellent water resistance and chemical resistance, the silicon-oxygen bond energy is high, and the surface energy is low, and the polymer modified by fluorine silicon has excellent water resistance; the introduction of the quaternary ammonium salt structure also gives the modified acrylic ester emulsion antibacterial properties, thereby giving the water-based two-component polyurethane varnish certain antibacterial properties.

[0029] Secondly, silica nanosheets are obtained by the reaction of tetraethoxysilane and 3-aminopropyltriethoxysilane, one side of which contains hydroxyl groups and the other side contains amino groups. The side containing hydroxyl groups is grafted with hydrophobic long chains by reacting with dodecyltrimethoxysilane, and the side containing amino groups is grafted with hydrophilic groups by reacting with cyanuric chloride and sodium sulfosalicylate, thereby obtaining amphiphilic silica nanosheets. The addition of silica nanosheets can give the water-based two-component polyurethane varnish good wear resistance. At the same time, the amphiphilic silica nanosheets can replace traditional emulsifiers, act as emulsifiers and stabilize the emulsion in the preparation process of modified acrylic emulsions; the hydrophilic side of the amphiphilic silica nanosheets, due to the introduction of sodium salicylate, allows the amphiphilic titanium dioxide nanosheets to absorb ultraviolet rays, thereby giving the water-based two-component polyurethane varnish anti-ultraviolet aging properties.

[0030] Finally, methyl methacrylate, butyl acrylate, hydroxypropyl methacrylate, quaternary ammonium caged siloxane, and amphiphilic silica nanosheets are reacted to prepare a modified acrylic emulsion. The hydroxyl groups on the hydroxypropyl methacrylate serve as cross-linking sites and are cross-linked with an isocyanate curing agent to form a paint film. DETAILED DESCRIPTION

[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0032] The wetting agent used in the following examples and comparative examples is Hydropalat 140; the defoaming agent is BYK-024; the isocyanate curing agent is XP-2655.

[0033] Example 1

[0034] A water-based two-component polyurethane varnish comprises the following preparation steps:

[0035] (1) Nonafluorohexyltrimethoxysilane, tetrahydrofuran, pure water, and sodium hydroxide were mixed uniformly in a mass ratio of 1:50:0.06:0.04, heated to 70° C. and refluxed for reaction for 5 h, cooled to room temperature and stirred for 15 h, and the tetrahydrofuran was removed by rotary evaporation under reduced pressure, and dried at 40° C. for 24 h to obtain a cage-type siloxane precursor;

[0036] (2) A cage-type siloxane precursor, triethylamine, and tetrahydrofuran were mixed at a mass ratio of 1:0.3:20 to obtain a cage-type siloxane precursor solution, 3-chloropropyltrichlorosilane and tetrahydrofuran were mixed at a mass ratio of 1:10, and the mixture was added dropwise to the cage-type siloxane precursor solution at 0°C at a dropping rate of 1 mL / min. After the addition was completed, the reaction was continued for 5 hours, the temperature was raised to room temperature, and the reaction was continued for 14 hours. The filtrate was filtered and the tetrahydrofuran in the filtrate was removed by vacuum rotary evaporation, and the mixture was washed with methanol 4 times and dried at 40°C for 24 hours to obtain a cage-type siloxane;

[0037] (3) mixing cage-type siloxane, potassium carbonate, 4-vinylpyridine and chloroform in a mass ratio of 1:0.3:0.7:15, heating to 80° C., reflux reaction for 24 h, cooling to room temperature, filtering and washing with chloroform 4 times, and drying at 40° C. for 24 h to obtain quaternary ammonium cage-type siloxane;

[0038] (4) n-decane and toluene were mixed in a mass ratio of 1:1 to obtain an n-decane-toluene solution; sodium dodecyl sulfate and pure water were mixed in a mass ratio of 1:3, and the pH was adjusted to 3 with a 2 mol / L hydrochloric acid aqueous solution to obtain an aqueous phase; tetraethoxysilane, 3-aminopropyltriethoxysilane, and n-decane-toluene solution were mixed in a mass ratio of 1:0.15:5 to obtain an oil phase; the aqueous phase and the oil phase were mixed in a mass ratio of 1:0.25, stirred at a speed of 1000 rpm / min, and then heated to 70°C, reacted for 12 hours, centrifuged at a speed of 5000 r / min for 10 minutes, and washed 4 times with anhydrous ethanol to obtain carbon dioxide Silicon hollow microspheres, using a cell crusher to crush the silicon dioxide hollow microspheres, the operating parameters of the cell crusher are working for 2s, pausing for 2s, working time for 60min, and power of 400W, and the crushed silicon dioxide hollow microspheres are dried at room temperature for 24h to obtain silicon dioxide nanosheets; the silicon dioxide nanosheets and toluene are mixed at a mass ratio of 1:150, and dodecyltrimethoxysilane with a mass of 2 times that of the silicon dioxide nanosheets and triethylamine with a mass of 0.1 times that of the silicon dioxide nanosheets are added under nitrogen protection, reacting at 80°C for 24h, filtering and washing with toluene 5 times, and drying at 40°C for 24h to obtain a modified silicon dioxide nanosheet precursor;

[0039] (5) mixing the modified silica nanosheet precursor and toluene in a mass ratio of 1:150, adding cyanuric chloride 5 times the mass of the silica nanosheet under nitrogen protection, reacting at 30° C. for 12 h, filtering and washing with toluene 5 times, and drying at 40° C. for 24 h to obtain the modified silica nanosheet;

[0040] (6) under nitrogen protection, the modified silica nanosheets, chlorobenzene, and anhydrous aluminum chloride were mixed in a mass ratio of 1:150:5, and under nitrogen protection, sodium sulfosalicylate was added in an amount 9 times the mass of the modified silica nanosheets, and the mixture was reacted at 40° C. for 17 h, filtered, washed with toluene 5 times, and dried at 40° C. for 24 h to obtain amphiphilic silica nanosheets; the amphiphilic silica nanosheets and pure water were mixed in a mass ratio of 1:20 to obtain an amphiphilic silica nanosheet dispersion;

[0041] (7) ammonium persulfate and pure water are mixed at a mass ratio of 1:10 to obtain an initiator solution; 20 parts by mass of methyl methacrylate, 20 parts by mass of butyl acrylate, 5 parts by mass of hydroxypropyl methacrylate, 10 parts by mass of quaternary ammonium salt caged siloxane, 10 parts by mass of modified silica nanosheet dispersion, 50 parts by mass of pure water, and 3 parts by mass of the initiator solution; methyl methacrylate, butyl acrylate, hydroxypropyl methacrylate, quaternary ammonium salt caged siloxane, amphiphilic silica nanosheet dispersion and pure water are mixed; and Stirring for 2 hours under protection at a stirring speed of 500 rpm / min to obtain a pre-emulsion; stirring 20% ​​of the pre-emulsion and the initiator solution at a mass ratio of 1:0.1 at 70°C for 12 hours at a stirring speed of 200 rpm / min, heating to 82°C, dripping the remaining 80% of the pre-emulsion at a dripping rate of 1 mL / min, and after the dripping is completed, continuing to heat to 92°C, keeping the temperature for 50 minutes and cooling to room temperature, using 25wt% ammonia water to adjust the pH to 6 to obtain a modified acrylate emulsion;

[0042] (8) Weighing 15 parts of pure water, 0.05 parts of a wetting agent, 0.1 parts of a defoaming agent, and 60 parts of a modified acrylic emulsion by weight; mixing the pure water, the wetting agent, the defoaming agent, and the modified acrylic emulsion, and stirring at 600 r / min for 30 min to obtain component A;

[0043] (9) Weigh 60 parts by mass of an isocyanate curing agent and 40 parts by mass of pure water, and stir the isocyanate curing agent and pure water at 600 r / min for 30 min to obtain component B;

[0044] (10) Component A and component B are mixed in a mass ratio of 4:1 and stirred evenly to obtain a water-based two-component polyurethane varnish.

[0045] Example 2

[0046] A water-based two-component polyurethane varnish comprises the following preparation steps:

[0047] (1) Nonafluorohexyltrimethoxysilane, tetrahydrofuran, pure water, and sodium hydroxide were mixed uniformly in a mass ratio of 1:55:0.07:0.045, heated to 70° C. and refluxed for 4.5 h, cooled to room temperature and stirred for 14.5 h, and the tetrahydrofuran was removed by vacuum rotary evaporation, and dried at 40° C. for 23 h to obtain a cage-type siloxane precursor;

[0048] (2) The cage-type siloxane precursor, triethylamine, and tetrahydrofuran were mixed in a mass ratio of 1:0.4:25 to obtain a cage-type siloxane precursor solution, 3-chloropropyltrichlorosilane and tetrahydrofuran were mixed in a mass ratio of 1:11, and the mixture was added dropwise to the cage-type siloxane precursor solution at 0°C at a dropping rate of 1 mL / min. After the addition was completed, the reaction was continued for 4.5 hours, and the temperature was raised to room temperature and the reaction was continued for 13 hours. The filtrate was filtered and the tetrahydrofuran in the filtrate was removed by vacuum rotary evaporation, and the mixture was washed with methanol 3 times and dried at 40°C for 23 hours to obtain a cage-type siloxane;

[0049] (3) mixing cage-type siloxane, potassium carbonate, 4-vinylpyridine and chloroform in a mass ratio of 1:0.4:0.8:17, heating to 75°C, reflux reaction for 24 hours, cooling to room temperature, filtering and washing with chloroform three times, and drying at 40°C for 23 hours to obtain quaternary ammonium cage-type siloxane;

[0050] (4) n-decane and toluene were mixed at a mass ratio of 1:1 to prepare an n-decane-toluene solution; sodium dodecyl sulfate and pure water were mixed at a mass ratio of 1:3, and the pH was adjusted to 3 with a 2 mol / L hydrochloric acid aqueous solution to obtain an aqueous phase; tetraethoxysilane, 3-aminopropyltriethoxysilane, and n-decane-toluene solution were mixed at a mass ratio of 1:0.17:5.5 to obtain an oil phase; the aqueous phase and the oil phase were mixed at a mass ratio of 1:0.25, stirred at a speed of 1000 rpm / min, and then heated to 70°C, reacted for 12 hours, centrifuged at a speed of 5000 r / min for 10 minutes, and washed three times with anhydrous ethanol to obtain dioxygen. The silica hollow microspheres were crushed by a cell crusher, the operating parameters of the cell crusher were working for 2s, pausing for 2s, working for 60min, and a power of 400W, and the crushed silica hollow microspheres were dried at room temperature for 24h to obtain silica nanosheets; the silica nanosheets and toluene were mixed at a mass ratio of 1:155, and 2.5 times the mass of the silica nanosheets of dodecyltrimethoxysilane and 0.2 times the mass of the silica nanosheets of triethylamine were added under nitrogen protection, reacted at 80°C for 24h, filtered, washed with toluene 4 times, and dried at 40°C for 23h to obtain a modified silica nanosheet precursor;

[0051] (5) mixing the modified silica nanosheet precursor and toluene in a mass ratio of 1:155, adding 5.5 times the mass of cyanuric chloride of the silica nanosheet under nitrogen protection, reacting at 27° C. for 11 h, filtering and washing with toluene 4 times, and drying at 40° C. for 23 h to obtain the modified silica nanosheet;

[0052] (6) under nitrogen protection, the modified silica nanosheets, chlorobenzene, and anhydrous aluminum chloride were mixed in a mass ratio of 1:155:5.5, and under nitrogen protection, 9.5 times the mass of the modified silica nanosheets sodium sulfosalicylate was added, reacted at 35° C. for 16 h, filtered and washed with toluene 4 times, and dried at 40° C. for 23 h to obtain amphiphilic silica nanosheets; the amphiphilic silica nanosheets and pure water were mixed in a mass ratio of 1:25 to obtain an amphiphilic silica nanosheet dispersion;

[0053] (7) ammonium persulfate and pure water are mixed at a mass ratio of 1:15 to obtain an initiator solution; 25 parts of methyl methacrylate, 25 parts of butyl acrylate, 7 parts of hydroxypropyl methacrylate, 15 parts of quaternary ammonium salt caged siloxane, 15 parts of modified silica nanosheet dispersion, 55 parts of pure water, and 4 parts of the initiator solution are weighed in parts by mass; methyl methacrylate, butyl acrylate, hydroxypropyl methacrylate, quaternary ammonium salt caged siloxane, amphiphilic silica nanosheet dispersion and pure water are mixed, and the mixture is heated under nitrogen protection. Stirring for 1.5 hours at a stirring speed of 500 rpm / min to obtain a pre-emulsion; stirring 20% ​​of the pre-emulsion and the initiator solution at a mass ratio of 1:0.15 at 65°C for 11 hours at a stirring speed of 200 rpm / min, heating to 81°C, dripping the remaining 80% of the pre-emulsion at a dripping rate of 1 mL / min, and after the dripping is completed, continuing to heat to 91°C, keeping the temperature for 45 minutes and cooling to room temperature, using 25wt% ammonia water to adjust the pH to 6.5 to obtain a modified acrylate emulsion;

[0054] (8) Weighing 20 parts of pure water, 0.07 parts of wetting agent, 0.2 parts of defoaming agent, and 65 parts of modified acrylic emulsion by weight; mixing the pure water, wetting agent, defoaming agent, and modified acrylic emulsion, and stirring at 550 r / min for 25 minutes to obtain component A;

[0055] (9) Weigh 65 parts by mass of an isocyanate curing agent and 45 parts by mass of pure water, and stir the isocyanate curing agent and pure water at 550 r / min for 25 min to obtain component B;

[0056] (10) Component A and component B are mixed at a mass ratio of 4.5:1 and stirred evenly to obtain a water-based two-component polyurethane varnish.

[0057] Example 3

[0058] A water-based two-component polyurethane varnish comprises the following preparation steps:

[0059] (1) Nonafluorohexyltrimethoxysilane, tetrahydrofuran, pure water, and sodium hydroxide were mixed uniformly in a mass ratio of 1:60:0.08:0.05, heated to 70° C. and refluxed for 4 h, cooled to room temperature and stirred for 14 h, and the tetrahydrofuran was removed by vacuum rotary evaporation, and dried at 40° C. for 22 h to obtain a cage-type siloxane precursor;

[0060] (2) A cage-type siloxane precursor, triethylamine, and tetrahydrofuran were mixed at a mass ratio of 1:0.5:30 to obtain a cage-type siloxane precursor solution, 3-chloropropyltrichlorosilane and tetrahydrofuran were mixed at a mass ratio of 1:12, and the mixture was added dropwise to the cage-type siloxane precursor solution at 0°C at a dropping rate of 1 mL / min. After the addition was completed, the reaction was continued for 4 hours, the temperature was raised to room temperature, and the reaction was continued for 12 hours. The filtrate was filtered and the tetrahydrofuran in the filtrate was removed by vacuum rotary evaporation, and the mixture was washed with methanol 3 times and dried at 40°C for 22 hours to obtain a cage-type siloxane;

[0061] (3) mixing cage-type siloxane, potassium carbonate, 4-vinylpyridine and chloroform in a mass ratio of 1:0.5:0.9:20, heating to 70° C., reflux reaction for 24 h, cooling to room temperature, filtering and washing with chloroform three times, and drying at 40° C. for 22 h to obtain quaternary ammonium cage-type siloxane;

[0062] (4) n-decane and toluene were mixed in a mass ratio of 1:1 to obtain a n-decane-toluene solution; sodium dodecyl sulfate and pure water were mixed in a mass ratio of 1:3, and the pH was adjusted to 3 with a 2 mol / L hydrochloric acid aqueous solution to obtain an aqueous phase; tetraethoxysilane, 3-aminopropyltriethoxysilane, and n-decane-toluene solution were mixed in a mass ratio of 1:0.2:6 to obtain an oil phase; the aqueous phase and the oil phase were mixed in a mass ratio of 1:0.25, stirred at a speed of 1000 rpm / min, and then heated to 70°C, reacted for 12 hours, centrifuged at a speed of 5000 r / min for 10 minutes, and washed three times with anhydrous ethanol to obtain a dichloromethane. Silicon hollow microspheres, using a cell crusher to crush the silicon dioxide hollow microspheres, the operating parameters of the cell crusher are working for 2s, pausing for 2s, working time for 60min, and power of 400W, and the crushed silicon dioxide hollow microspheres are dried at room temperature for 24h to obtain silicon dioxide nanosheets; the silicon dioxide nanosheets and toluene are mixed at a mass ratio of 1:160, and dodecyltrimethoxysilane 3 times the mass of the silicon dioxide nanosheets and triethylamine 0.3 times the mass of the silicon dioxide nanosheets are added under nitrogen protection, reacting at 80°C for 24h, filtering and washing with toluene 4 times, and drying at 40°C for 22h to obtain a modified silicon dioxide nanosheet precursor;

[0063] (5) mixing the modified silica nanosheet precursor and toluene in a mass ratio of 1:160, adding 6 times the mass of cyanuric chloride of the silica nanosheet under nitrogen protection, reacting at 25°C for 10 hours, filtering and washing with toluene 4 times, and drying at 40°C for 22 hours to obtain modified silica nanosheets;

[0064] (6) under nitrogen protection, the modified silica nanosheets, chlorobenzene, and anhydrous aluminum chloride were mixed in a mass ratio of 1:160:6, and under nitrogen protection, sodium sulfosalicylate 10 times the mass of the modified silica nanosheets was added, reacted at 30° C. for 15 h, filtered and washed with toluene 4 times, and dried at 40° C. for 22 h to obtain amphiphilic silica nanosheets; the amphiphilic silica nanosheets and pure water were mixed in a mass ratio of 1:30 to obtain an amphiphilic silica nanosheet dispersion;

[0065] (7) ammonium persulfate and pure water are mixed at a mass ratio of 1:20 to obtain an initiator solution; 30 parts by mass of methyl methacrylate, 30 parts by mass of butyl acrylate, 10 parts by mass of hydroxypropyl methacrylate, 20 parts by mass of quaternary ammonium salt caged siloxane, 20 parts by mass of modified silica nanosheet dispersion, 60 parts by mass of pure water, and 5 parts by mass of the initiator solution; methyl methacrylate, butyl acrylate, hydroxypropyl methacrylate, quaternary ammonium salt caged siloxane, amphiphilic silica nanosheet dispersion and pure water are mixed; and Stirring for 1 hour under protection at a stirring speed of 500 rpm / min to obtain a pre-emulsion; stirring 20% ​​of the pre-emulsion and the initiator solution at a mass ratio of 1:0.2 at 60°C for 10 hours at a stirring speed of 200 rpm / min, heating to 80°C, dripping the remaining 80% of the pre-emulsion at a dripping rate of 1 mL / min, and after the dripping is completed, continuing to heat to 90°C, keeping the temperature for 40 minutes and cooling to room temperature, using 25wt% ammonia water to adjust the pH to 7 to obtain a modified acrylate emulsion;

[0066] (8) Weighing 25 parts of pure water, 0.1 parts of wetting agent, 0.3 parts of defoaming agent, and 70 parts of modified acrylic emulsion by weight; mixing the pure water, wetting agent, defoaming agent, and modified acrylic emulsion, and stirring at 500 r / min for 20 minutes to obtain component A;

[0067] (9) Weigh 70 parts by mass of an isocyanate curing agent and 50 parts by mass of pure water, and stir the isocyanate curing agent and pure water at 500 r / min for 20 min to obtain component B;

[0068] (10) Component A and component B are mixed in a mass ratio of 5:1 and stirred evenly to obtain a water-based two-component polyurethane varnish.

[0069] Comparative Example 1

[0070] The preparation method of the water-based two-component polyurethane varnish of Comparative Example 1 is different from that of Example 2 in that step (3) is not included, and step (7) is modified as follows: ammonium persulfate and pure water are mixed in a mass ratio of 1:15 to obtain an initiator solution; 25 parts of methyl methacrylate, 25 parts of butyl acrylate, 7 parts of hydroxypropyl methacrylate, 15 parts of caged siloxane, 15 parts of modified silica nanosheet dispersion, 55 parts of pure water, and 4 parts of the initiator solution are weighed in parts by mass; methyl methacrylate, butyl acrylate, hydroxypropyl methacrylate, caged siloxane, amphiphilic silica nanosheet dispersion, and 15 parts of modified silica nanosheet dispersion are mixed; and the mixture is stirred for 2 hours. The silicon nanosheet dispersion and pure water are mixed, stirred for 1.5 hours under nitrogen protection at a stirring speed of 500 rpm / min to obtain a pre-emulsion; 20% of the pre-emulsion and the initiator solution are stirred at a mass ratio of 1:0.15 at 65°C for 11 hours at a stirring speed of 200 rpm / min, the temperature is raised to 81°C, and the remaining 80% of the pre-emulsion is added dropwise at a dropping rate of 1 mL / min. After the addition is completed, the temperature is continued to be raised to 91°C, kept warm for 45 minutes and cooled to room temperature, and the pH is adjusted to 6.5 with 25wt% ammonia water to obtain a modified acrylate emulsion.

[0071] Comparative Example 2

[0072] The preparation method of the water-based two-component polyurethane varnish of Comparative Example 2 differs from that of Example 2 in that steps (1), (2) and (3) are not included, and step (7) is modified as follows: ammonium persulfate and pure water are mixed in a mass ratio of 1:15 to obtain an initiator solution; 25 parts by mass of methyl methacrylate, 25 parts by mass of butyl acrylate, 7 parts by mass of hydroxypropyl methacrylate, 15 parts by mass of a dispersion of modified silica nanosheets, 55 parts by mass of pure water, and 4 parts by mass of the initiator solution are weighed; methyl methacrylate, butyl acrylate, hydroxypropyl methacrylate, amphiphilic silica nanosheets are added to the mixture; The flake dispersion and pure water are mixed, stirred for 1.5 hours under nitrogen protection at a stirring speed of 500 rpm / min to obtain a pre-emulsion; 20% of the pre-emulsion and the initiator solution are stirred at a mass ratio of 1:0.15 at 65°C for 11 hours at a stirring speed of 200 rpm / min, the temperature is raised to 81°C, and the remaining 80% of the pre-emulsion is added dropwise at a dropping rate of 1 mL / min. After the addition is completed, the temperature is continued to be raised to 91°C, kept warm for 45 minutes, cooled to room temperature, and 25 wt% of ammonia water is used to adjust the pH to 6.5 to obtain a modified acrylate emulsion.

[0073] Test Example 1

[0074] Water resistance and UV resistance testing

[0075] Water resistance test: According to the standard GB / T 1733-1993, the water resistance test was carried out by the "immersion test method". The water-based two-component polyurethane varnish prepared in the examples and comparative examples was applied on a dry and clean tinplate sheet with a film applicator. After being placed at room temperature for 168 hours, the tinplate sheet was immersed in pure water for 24 hours. The iron sheet was taken out, and the water on the surface of the paint film was absorbed with filter paper. The paint film was observed to see whether it peeled off, wrinkled, bubbling, lost gloss, changed color, rusted, etc. The results are shown in Table 1.

[0076] Table 1 Water resistance and UV aging resistance test results

[0077]

[0078] Anti-ultraviolet aging performance test: The water-based two-component polyurethane varnish prepared in the embodiment and the comparative example was coated on a dry and clean tinplate sheet with a film applicator, and the tinplate sheet was placed in a UV aging box for 168 hours, and then taken out to observe whether the paint film has peeling, wrinkling, blistering, gloss loss, discoloration, rust, etc. The temperature in the UV aging box is 50°C, the wavelength of the ultraviolet light is 340nm, the light power is 40W, and the distance between the paint film and the light source is 50mm. The results are shown in Table 1.

[0079] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 1, it can be found that the water-based two-component polyurethane varnish prepared in the present invention has good water resistance and anti-ultraviolet aging performance.

[0080] By comparison, the appearance of the paint film of Examples 1 to 3 is better than that of the paint film of Comparative Examples 1 to 3, which shows that first, nonafluorohexyltrimethoxysilane is used to obtain a cage-type siloxane precursor, the cage-type siloxane precursor is reacted with 3-chloropropyltrichlorosilane to obtain a cage-type siloxane containing nonafluorohexyl and monochloropropyl, and then reacted with 4-vinylpyridine to form a quaternary ammonium salt, and a double bond is introduced into the cage-type siloxane for subsequent polymerization with an acrylate monomer; the fluorine atom has a large electronegativity, a small radius, and a large bond energy, and the fluorine-containing monomer polymer has excellent water resistance and chemical resistance, the silicon-oxygen bond energy is high, the surface energy is low, and the polymer modified by fluorine silicon has excellent water resistance.

[0081] Secondly, silica nanosheets are obtained by the reaction of tetraethoxysilane and 3-aminopropyltriethoxysilane, which have hydroxyl groups on one side and amino groups on the other side. The hydroxyl side is grafted with hydrophobic long chains by reacting with dodecyltrimethoxysilane, and the amino side is grafted with hydrophilic groups by reacting with cyanuric chloride and sodium sulfosalicylate. Due to the introduction of sodium salicylate, the hydrophilic side of the amphiphilic silica nanosheets can absorb ultraviolet rays, thereby giving the water-based two-component polyurethane varnish anti-ultraviolet aging properties.

[0082] Finally, methyl methacrylate, butyl acrylate, hydroxypropyl methacrylate, quaternary ammonium caged siloxane, and amphiphilic silica nanosheets are reacted to prepare a modified acrylic emulsion. The hydroxyl groups on the hydroxypropyl methacrylate serve as cross-linking sites and are cross-linked with an isocyanate curing agent to form a paint film.

[0083] Test Example 2

[0084] Antimicrobial performance testing

[0085] The antibacterial rate of the water-based two-component polyurethane varnish prepared in the examples and comparative examples was tested according to the standard GB / T 21866-2008 "Antibacterial property determination method and antibacterial effect of antibacterial coatings (paint films)". The results are shown in Table 2.

[0086] Table 2 Antibacterial performance test results

[0087] Antibacterial rate Antibacterial rate Example 1 95.9% Comparative Example 1 24.1% Example 2 95.6% Comparative Example 2 20.4% Example 3 96.7% Comparative Example 3 95.4%

[0088] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 2, it can be found that the water-based two-component polyurethane varnish prepared in the present invention has good antibacterial properties.

[0089] By comparison, the antibacterial rates of Examples 1 to 3 are greater than those of Comparative Examples 1 to 2, indicating that nonafluorohexyltrimethoxysilane is used to obtain a cage-type siloxane precursor, and the cage-type siloxane precursor reacts with 3-chloropropyltrichlorosilane to obtain a cage-type siloxane, which contains nonafluorohexyl and monochloropropyl groups, and then reacts with 4-vinylpyridine to form a quaternary ammonium salt. The introduction of the quaternary ammonium salt structure gives the modified acrylic emulsion antibacterial properties, thereby giving the water-based two-component polyurethane varnish certain antibacterial properties.

[0090] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A water-based two-component polyurethane varnish, characterized in that: The invention comprises component A and component B, wherein the component A comprises pure water, a wetting agent, a defoaming agent, and a modified acrylic emulsion; and the component B comprises an isocyanate curing agent and pure water; The preparation method of the modified acrylic ester emulsion is: (1) Nonafluorohexyltrimethoxysilane, tetrahydrofuran, pure water and sodium hydroxide were mixed uniformly in a mass ratio of 1:(50-60):(0.06-0.08):(0.04-0.05), heated to 70°C and refluxed for 4-5 hours, cooled to room temperature and stirred for 14-15 hours, and the tetrahydrofuran was removed by vacuum rotary evaporation, and dried at 40°C for 22-24 hours to obtain a cage-type siloxane precursor; (2) Mix the cage-type siloxane precursor, triethylamine and tetrahydrofuran in a mass ratio of 1:(0.3-0.5):(20-30) to obtain a cage-type siloxane precursor solution, mix 3-chloropropyltrichlorosilane and tetrahydrofuran in a mass ratio of 1:(10-12) to obtain a cage-type siloxane precursor solution, and add the mixture dropwise to the cage-type siloxane precursor solution at a rate of 1 mL / min at 0°C. After the addition is completed, continue the reaction for 4-5 hours, heat the mixture to room temperature and continue the reaction for 12-14 hours, filter the filtrate, remove tetrahydrofuran from the filtrate by vacuum rotary evaporation, wash the mixture with methanol for 3-4 times, and dry the mixture at 40°C for 22-24 hours to obtain a cage-type siloxane; (3) Mix cage-type siloxane, potassium carbonate, 4-vinylpyridine and chloroform in a mass ratio of 1:(0.3-0.5):(0.7-0.9):(15-20), heat to 70-80°C, reflux for 24 hours, cool to room temperature, filter and wash with chloroform for 3-4 times, and dry at 40°C for 22-24 hours to obtain quaternary ammonium cage-type siloxane; (4) Mixing silica nanosheets and toluene in a mass ratio of 1:(150-160), adding 2-3 times the mass of silica nanosheets of dodecyltrimethoxysilane and 0.1-0.3 times the mass of silica nanosheets of triethylamine under nitrogen protection, reacting at 80°C for 24h, filtering and washing with toluene for 4-5 times, and drying at 40°C for 22-24h to obtain a modified silica nanosheet precursor; (5) Mixing the modified silica nanosheet precursor and toluene in a mass ratio of 1:(150-160), adding 5-6 times the mass of cyanuric chloride of the silica nanosheet under nitrogen protection, reacting at 25-30°C for 10-12h, filtering and washing with toluene for 4-5 times, and drying at 40°C for 22-24h to obtain modified silica nanosheets; (6) Under nitrogen protection, the modified silica nanosheets, chlorobenzene, and anhydrous aluminum chloride are mixed in a mass ratio of 1:(150-160):(5-6), and under nitrogen protection, 9-10 times the mass of sodium sulfosalicylate of the modified silica nanosheets is added, reacting at 30-40°C for 15-17h, filtering and washing with toluene 4-5 times, and drying at 40°C for 22-24h to obtain amphiphilic silica nanosheets; the amphiphilic silica nanosheets and pure water are mixed in a mass ratio of 1:(20-30) to obtain an amphiphilic silica nanosheet dispersion; (7) ammonium persulfate and pure water are mixed in a mass ratio of 1:(10-20) to obtain an initiator solution; methyl methacrylate, butyl acrylate, hydroxypropyl methacrylate, quaternary ammonium salt cage siloxane, amphiphilic silica nanosheet dispersion and pure water are mixed, and stirred for 1-2 hours under nitrogen protection at a stirring speed of 500 r / min to obtain a pre-emulsion; 20% of the pre-emulsion and the initiator solution are stirred at a mass ratio of 1:(0.1-0.2) at 60-70°C for 10-12 hours at a stirring speed of 200 r / min, and the temperature is raised to 80-82°C, and the remaining 80% of the pre-emulsion is added dropwise at a dropping rate of 1 mL / min. After the addition is completed, the temperature is continued to be raised to 90-92°C, and the temperature is kept for 40-50 minutes and then cooled to room temperature. 25wt% ammonia water is used to adjust the pH to 6-7 to obtain a modified acrylate emulsion; The preparation method of the silica nanosheets in step (4) is as follows: sodium dodecyl sulfate and pure water are mixed in a mass ratio of 1:3, the pH is adjusted to 3 with a 2 mol / L hydrochloric acid aqueous solution to obtain an aqueous phase, tetraethoxysilane, 3-aminopropyltriethoxysilane, and n-decane-toluene solution are mixed in a mass ratio of 1:(0.15-0.2):(5-6) to obtain an oil phase, the aqueous phase and the oil phase are mixed in a mass ratio of 1:0.25, stirred at a speed of 1000 r / min, heated to 70°C, reacted for 12 hours, centrifuged at a speed of 5000 r / min for 10 minutes, and washed 3-4 times with anhydrous ethanol to obtain silica hollow microspheres, and the silica hollow microspheres are crushed using a cell crusher. The operating parameters of the cell crusher are working for 2 seconds, pausing for 2 seconds, working time for 60 minutes, and power of 400W. The crushed silica hollow microspheres are dried at room temperature for 24 hours to obtain silica nanosheets.

2. A method for preparing a water-based two-component polyurethane varnish according to claim 1, characterized in that: The method comprises the following preparation steps: (1) Nonafluorohexyltrimethoxysilane, tetrahydrofuran, pure water and sodium hydroxide were mixed uniformly in a mass ratio of 1:(50-60):(0.06-0.08):(0.04-0.05), heated to 70°C and refluxed for 4-5 hours, cooled to room temperature and stirred for 14-15 hours, and the tetrahydrofuran was removed by vacuum rotary evaporation, and dried at 40°C for 22-24 hours to obtain a cage-type siloxane precursor; (2) Mix the cage-type siloxane precursor, triethylamine and tetrahydrofuran in a mass ratio of 1:(0.3-0.5):(20-30) to obtain a cage-type siloxane precursor solution, mix 3-chloropropyltrichlorosilane and tetrahydrofuran in a mass ratio of 1:(10-12) to obtain a cage-type siloxane precursor solution, and add the mixture dropwise to the cage-type siloxane precursor solution at a rate of 1 mL / min at 0°C. After the addition is completed, continue the reaction for 4-5 hours, heat the mixture to room temperature and continue the reaction for 12-14 hours, filter the filtrate, remove tetrahydrofuran from the filtrate by vacuum rotary evaporation, wash the mixture with methanol for 3-4 times, and dry the mixture at 40°C for 22-24 hours to obtain a cage-type siloxane; (3) Mix cage-type siloxane, potassium carbonate, 4-vinylpyridine and chloroform in a mass ratio of 1:(0.3-0.5):(0.7-0.9):(15-20), heat to 70-80°C, reflux for 24 hours, cool to room temperature, filter and wash with chloroform for 3-4 times, and dry at 40°C for 22-24 hours to obtain quaternary ammonium cage-type siloxane; (4) Mixing silica nanosheets and toluene in a mass ratio of 1:(150-160), adding 2-3 times the mass of silica nanosheets of dodecyltrimethoxysilane and 0.1-0.3 times the mass of silica nanosheets of triethylamine under nitrogen protection, reacting at 80°C for 24h, filtering and washing with toluene for 4-5 times, and drying at 40°C for 22-24h to obtain a modified silica nanosheet precursor; (5) Mixing the modified silica nanosheet precursor and toluene in a mass ratio of 1:(150-160), adding 5-6 times the mass of cyanuric chloride of the silica nanosheet under nitrogen protection, reacting at 25-30°C for 10-12h, filtering and washing with toluene for 4-5 times, and drying at 40°C for 22-24h to obtain modified silica nanosheets; (6) Under nitrogen protection, the modified silica nanosheets, chlorobenzene, and anhydrous aluminum chloride are mixed in a mass ratio of 1:(150-160):(5-6), and under nitrogen protection, 9-10 times the mass of sodium sulfosalicylate of the modified silica nanosheets is added, reacting at 30-40°C for 15-17h, filtering and washing with toluene 4-5 times, and drying at 40°C for 22-24h to obtain amphiphilic silica nanosheets; the amphiphilic silica nanosheets and pure water are mixed in a mass ratio of 1:(20-30) to obtain an amphiphilic silica nanosheet dispersion; (7) ammonium persulfate and pure water are mixed in a mass ratio of 1:(10-20) to obtain an initiator solution; methyl methacrylate, butyl acrylate, hydroxypropyl methacrylate, quaternary ammonium cage siloxane, amphiphilic silica nanosheet dispersion and pure water are mixed, and stirred for 1-2 hours under nitrogen protection at a stirring speed of 500 r / min to obtain a pre-emulsion; 20% of the pre-emulsion and the initiator solution are stirred at a mass ratio of 1:(0.1-0.2) at 60-70°C for 10-12 hours at a stirring speed of 200 r / min, and the temperature is raised to 80-82°C, and the remaining 80% of the pre-emulsion is added dropwise at a dropping rate of 1 mL / min. After the addition is completed, the temperature is continued to be raised to 90-92°C, and the temperature is lowered to room temperature after keeping the temperature for 40-50 minutes, and the pH is adjusted to 6-7 with 25wt% ammonia water to obtain a modified acrylate emulsion; (8) Weigh 15-25 parts of pure water, 0.05-0.1 parts of wetting agent, 0.1-0.3 parts of defoaming agent, and 60-70 parts of modified acrylic emulsion by weight; mix the pure water, wetting agent, defoaming agent, and modified acrylic emulsion, and stir at 500-600 r / min for 20-30 minutes to obtain component A; (9) Weigh 60-70 parts by mass of isocyanate curing agent and 40-50 parts by mass of pure water, and stir the isocyanate curing agent and pure water at 500-600 r / min for 20-30 min to obtain component B; (10) Component A and component B are mixed in a mass ratio of (4-5):1 and stirred evenly to obtain a water-based two-component polyurethane varnish; The preparation method of the silica nanosheets in step (4) is as follows: sodium dodecyl sulfate and pure water are mixed in a mass ratio of 1:3, the pH is adjusted to 3 with a 2 mol / L hydrochloric acid aqueous solution to obtain an aqueous phase, tetraethoxysilane, 3-aminopropyltriethoxysilane, and n-decane-toluene solution are mixed in a mass ratio of 1:(0.15-0.2):(5-6) to obtain an oil phase, the aqueous phase and the oil phase are mixed in a mass ratio of 1:0.25, stirred at a speed of 1000 r / min, heated to 70°C, reacted for 12 hours, centrifuged at a speed of 5000 r / min for 10 minutes, and washed 3-4 times with anhydrous ethanol to obtain silica hollow microspheres, and the silica hollow microspheres are crushed using a cell crusher. The operating parameters of the cell crusher are working for 2 seconds, pausing for 2 seconds, working time for 60 minutes, and power of 400W. The crushed silica hollow microspheres are dried at room temperature for 24 hours to obtain silica nanosheets.

3. The method for preparing a water-based two-component polyurethane varnish according to claim 2, characterized in that: The amounts of methyl methacrylate, butyl acrylate, hydroxypropyl methacrylate, quaternary ammonium salt cage-type siloxane, amphiphilic silica nanosheet dispersion, pure water, and initiator solution in step (7) are as follows: by mass: 20-30 parts of methyl methacrylate, 20-30 parts of butyl acrylate, 5-10 parts of hydroxypropyl methacrylate, 10-20 parts of quaternary ammonium salt cage-type siloxane, 10-20 parts of modified silica nanosheet dispersion, 50-60 parts of pure water, and 3-5 parts of initiator solution.

4. The method for preparing a water-based two-component polyurethane varnish according to claim 2, characterized in that: The wetting agent model in step (8) is Hydropalat 140; the defoaming agent model is BYK-024.

5. The method for preparing a water-based two-component polyurethane varnish according to claim 2, characterized in that: The isocyanate curing agent in step (9) is Bayhydur ® XP-2655.

6. The method for preparing a water-based two-component polyurethane varnish according to claim 2, characterized in that: The n-decane-toluene solution is prepared by mixing n-decane and toluene in a mass ratio of 1:

1.

7. A method for using the water-based two-component polyurethane varnish prepared by the method for preparing the water-based two-component polyurethane varnish according to any one of claims 2 to 6, characterized in that: The method of use is as follows: component A and component B are mixed in a mass ratio of (4-5):1 and stirred evenly to obtain a water-based two-component polyurethane varnish, and the water-based two-component polyurethane varnish is applied on a substrate by roller coating or spraying. The water-based two-component polyurethane varnish needs to be prepared and used immediately, and the coating is completed within 0-2 hours.

Citation Information

Patent Citations

  • New catalysts for the cross-linking of functional silanes or functional siloxanes, particularly with substrates

    CN102149759A

  • Polymer grafting modified silicon dioxide nanosheet as well as preparation method and use thereof

    CN104610574A